‘Who’s out there?’ — Strengthening Internet Communication for Agriculture Through Consideration of Audience Dimensions and User Needs - Margot Emery (Journal of Applied Communications, 1999)
Success in Internet publishing and communications has less to do with mastery of HTML and listserv management than with using a set of skills agricultural communicators already have in abundance: understanding of audience, the forms of content that audience wants, and how best to deliver it to them. Yet a 1997 study found these issues unresolved in much of the Internet activity by state agricultural experiment stations. Careful thought about audience, measurement, and medium can help agricultural communicators enhance the effectiveness of their on-line activity and capitalize on new opportunities presented by emerging global data centers for agricultural information.